Implikasi Kebijakan Indonesia dalam Menangani Kasus Pencemaran Lingkungan oleh PT. Freeport terhadap Keamanan Manusia di Mimika Papua - Astuti, Amelia Dwi; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Multinational corporations increasingly spread out across developing countries that haveresources. The presence of multinational corporation is opportune in improving investmentclimate but it's also causing pollution and environmental damage in countries where thecorporations operate. One of the operations is a mining activity by PT. Freeport in Mimika,Papua. The subsidiary of this corporation, Mac.Moran Coper Inc, manages miningresources asset in the form of copper and gold and has been operated since 1967 inIndonesia. Problem arises as a result of the polluting environment mining activity thatstarting to make people disturbed and starting to get condemned by environmentalists. Alocal non-governmental organization, Wahana Lingkungan Hidup, released an independentreport about impacts of pollution and environmental damage. This research is intended todicuss about Indonesia's policy in addressing environmental pollution and damage case byPT. Freeport's mining activity which affects human security. This research uses qualitativemethod with descriptive-explanative type with literature and technique study. Toanswering the question, this research used Human Security Concept and Elite Theory tolook at Indonesian policy by interviewing Walhi representatives and the Ministry of theEnvironment. The results of this study indicate that two different regimes that are SusiloBambang Yudhoyono and Joko Widodo have not been able to solve the case ofenvironmental pollution by PT. Freeport to conduct negotiations in order to review theextension of contract PT. Freeport in Indonesia.